2022
DOI: 10.1038/s41598-022-14203-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in co-abundant bacteriome in colorectal cancer and its persistence after surgery: a pilot study

Abstract: There is growing interest in the role of gut microbiome in colorectal cancer (CRC), ranging from screening to disease recurrence. Our study aims to identify microbial markers characteristic of CRC and to examine if changes in bacteriome persist after surgery. Forty-nine fecal samples from 25 non-cancer (NC) individuals and 12 CRC patients, before and 6-months after surgery, were collected for analysis by bacterial 16S rRNA gene sequencing. Bacterial richness and diversity were reduced, while pro-carcinogenic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Similar evidence was suggested by the Malaysian population studied by Png et al [ 53 ]. They evaluated forty-nine fecal samples from 25 noncancer (NC) individuals and 12 CRC patients, before and 6 months after surgery, performing analysis through bacterial 16S rRNA gene sequencing.…”
Section: Which Microbes and Which Molecular Pathways After Gastrointe...supporting
confidence: 90%
“…Similar evidence was suggested by the Malaysian population studied by Png et al [ 53 ]. They evaluated forty-nine fecal samples from 25 noncancer (NC) individuals and 12 CRC patients, before and 6 months after surgery, performing analysis through bacterial 16S rRNA gene sequencing.…”
Section: Which Microbes and Which Molecular Pathways After Gastrointe...supporting
confidence: 90%
“…Our results are consistent with previous findings of associations of GM in tumorigenesis. In particular, our cohorts highlighted an increase in Prevotella, Fusobacteria, and Bacteroides in BC patients, all widely reported to be associated both with tumorigenesis and response to therapy [19][20][21][22]. In addition to individual associations, our real-world cohorts from both institutions showed similar clustering patterns across communities (groups I-III) and association with chemotherapy response.…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, three other Bacteroides species were increased in polyps and cancers compared to healthy controls. B. vulgatus has been shown to decrease in abundance after CRC surgery and could potentially have a role in CRC [ 45 ]. Yachida et al investigated the tumor microbiome in different stages of CRC and showed that Phascolarctobacterium was increased in early stages of colorectal disease [ 46 ].…”
Section: Discussionmentioning
confidence: 99%